A Usability Framework to Influence the Intention to Use Mobile Fitness Applications in South Africa - Bulelani Ngamntwini; Liezel Cilliers (Reshaping Sustainable Development Goals Implementation in the World: Proceeding of 7th International Conference on Business and Management Dynamics, 2021)
On the African continent, South Africa has one of the highest prevalence of obese people. Forty-six percent of the adults in South Africa are physically inactive. There are numerous methods, such as fitness applications, that can be used to increase physical inactivity. However, the uptake of mobile fitness applications in South Africa has been found to be poor with one of the reasons being usability challenges. The purpose of this study was to develop a usability framework to influence users’ usage intentions to make use of mobile fitness applications in South Africa. A questionnaire was used to collect quantitative data from 377 respondents that have used mobile fitness applications in the past. A response rate of 80.90% was recorded (305 responses). To analyse the data, Pearson correlation was used to determine the relationships between the various hypotheses. According to the study findings, there are four usability factors that contribute to the intention of users to make use of mobile fitness applications. These factors are Efficiency, Effectiveness, Satisfaction and Learnability. The study therefore recommends that for a mobile fitness application to be successful, these four factors must be considered and incorporated by developers when designing the applications.